2018
DOI: 10.17577/ijertv7is110004
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of using Sewage Effluent from Different Water Treatment Plants in Different Cities of Saudi Arabia for Agricultural Reuse

Abstract: A comparative study was conducted to test the efficiencies of 7 sewage water treatment plants, 4 in Jeddah, Bani-Malik, Al-Balad, Al-Khomrah, Hael, one in Makkah, one in Abha and one in Taif city in Saudi Arabia. The plants were installed for the treatment of the cities domestic and industrial wastewater effluent. The parameters studied included the physiological, chemical and biological characteristics treated sewage water (effluent) of the treatment plants. The 7 plants vary in their efficiencies to eliminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…According to [25], the pH of wastewater has a significant role in determining how readily available potentially toxic elements are to the plant, and how easily they dissolve in the soil. This result is in line with some earlier studies that established the alkaline composition of the effluent water stream in wadi Al-Khumra [26,27]. Plant growth is better at a pH of 7 or higher since all the nutrients of the soil become easily accessible at that pH value [28].…”
Section: Water Samples Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…According to [25], the pH of wastewater has a significant role in determining how readily available potentially toxic elements are to the plant, and how easily they dissolve in the soil. This result is in line with some earlier studies that established the alkaline composition of the effluent water stream in wadi Al-Khumra [26,27]. Plant growth is better at a pH of 7 or higher since all the nutrients of the soil become easily accessible at that pH value [28].…”
Section: Water Samples Analysissupporting
confidence: 91%
“…Therefore, it is acceptable to reuse this water to irrigate ornamentals and nonfeeding plants growing close to the sewage stream where the water samples were collected. These findings corroborate those of the authors of [27], who found that treated wastewater in some treatment plants in Saudi Arabia can be used to irrigate agricultural fields simply and safely in terms of pH, EC, inorganic solutes, and potentially toxic elements.…”
Section: Water Samples Analysissupporting
confidence: 90%
See 1 more Smart Citation